HUBUNGAN MORFOLOGI DAN KEKUATAN OTOT QUADRICEPS FEMORIS DENGAN PATELLO FEMORAL PAIN SYNDROME DAN PERFORMA FUNGSIONAL PADA ATLET LEVEL 1 - Ni Putu Diah Asyana Putri; Adhitya, I Putu Gde Surya; Dewi, Anak Ayu Nyoman Trisna Narta (PT. Kesehatan Gerak Fungsi Tubuh, 2024)
Background: Patellofemoral pain syndrome (PFPS) is a clinical condition characterized by anterior knee pain common in athletes. Many factors cause (PFPS), one of which is the weakness of the quadriceps femoris (QF) muscle. Weakness of the QF muscle causes the knee to be unstable, which may affect an athlete's functional performance. The purpose of this literature review was to determine the relationship of QF muscle morphology and strength to PFPS and functional performance in level 1 athletes. Methods: This study used a literature review method. Articles were searched through PubMed and Google Scholar using the keywords